STUDI EMPIRIS MODEL PERTUMBUHAN EKONOMI SOLLOW: PENDEKATAN PARTIAL ADJUSTMENT MODEL (Studi Kasus: Kota Salatiga Tahun 2000-2020) - Angela Gracia Permata Hati; Birgitta Dian Saraswati (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
Economic growth is the main indicator for measuring people's welfare. According to the Sollow economic growth model, economic growth is influenced by factors of labor production and savings. This study aims to analyze the effect of the number of workers and the amount of savings on the level of economic growth in the City of Salatiga. By using the partial adjustment model method with the 2000-2020 time period, this study shows that labor and savings have a positive and significant effect on economic growth in the City of Salatiga both in the short and long term. This indicates that the output is produced under an increasing product marginal condition.